ORGANIZATIONAL ISSUES OF AUDIT IN UZBEKISTAN - Nazarova Kamola Sattorali qizi (American Journals, 2026)
This article is devoted to the issues of improving the organization of audit in the practice of Uzbekistan. The introductory part of the article reveals the essence of the organization and conduct of audit in the Republic and the relevance of research in this area. It also describes the research methods used to cover the content of the article, a review of the relevant literature, an analysis of the main indicators of audit activity in Uzbekistan, practical problems of organizing audit, organizational stages of audit, and conclusions reached as a result of the research.
Keywords: Audit inspections, audit service, auditor, audit organization, audit client, audit planning, audit conclusion, summary and evaluation of audit results, final stage of audit.